2000
DOI: 10.1046/j.1365-2362.2000.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of platelet density and volume measurements to estimate the severity of pre‐eclampsia

Abstract: The present work demonstrates considerable platelet alterations in pre-eclampsia. We failed to show granulocyte involvement in the pathogenesis of the disease. Severe pre-eclampsia is related to elevated mean platelet volumes. The latter parameter is associated with disturbed density distribution. It appears possible to estimate disease severity from measurements of platelet density and volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 16 publications
5
53
1
14
Order By: Relevance
“…Impaired platelet activation, both in the form of decreased platelet count and increased MPV, were associated with severity of HT in patients with PE in our study. Similar to our observations, Dundar et al and Jaremo et al reported a signifi cant relationship between MPV and PE (7,8) . Although the rapid turnover of platelets has been put forward as an explanation for this decrease in platelet count and increase in MPV, that study had a small sample size and did not investigate NLR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Impaired platelet activation, both in the form of decreased platelet count and increased MPV, were associated with severity of HT in patients with PE in our study. Similar to our observations, Dundar et al and Jaremo et al reported a signifi cant relationship between MPV and PE (7,8) . Although the rapid turnover of platelets has been put forward as an explanation for this decrease in platelet count and increase in MPV, that study had a small sample size and did not investigate NLR.…”
Section: Discussionsupporting
confidence: 92%
“…Despite previous studies showing an association between hematological parameters and PE, the relationship between the severity of hypertension and hematologic parameters in preeclamptic women has not been thoroughly studied (7,8) . This study was undertaken to investigate the relationship between the severity of hypertension (HT) and hematologic parameters in preeclamptic women that can be measured by a simple complete blood count.…”
Section: Introductionmentioning
confidence: 99%
“…The previous data on circulating MPO levels in patients with preeclampsia were conflicting 28 ; our data agree with studies reporting increased MPO in the circulation of women with preeclampsia. 1,29 Unlike the placenta, circulating MPO levels did not significantly increase with gestation. The most plausible source of MPO in the circulation is activated inflammatory cells in either the circulation or tissue.…”
Section: Discussionmentioning
confidence: 84%
“…Preeclampsia is associated with increased neutrophil counts. 1 Peripheral blood leukocytes are activated in women with normal third trimester pregnancies compared with nonpregnant patients. Leukocytes in normal pregnancy have increased markers of activation (CD11b, CD14, CD64, and intracellular reactive oxygen species), which are further increased in preeclampsia.…”
mentioning
confidence: 99%
“…Due to a technical failure, platelet reactivity, as judged from the platelet fibrinogen binding after agonist provocation, was not analysed in the healthy control group. An enzyme-linked immunosorbent assay (R&D Systems, Minneapolis, MN, USA) was used to analyse soluble P-selectin [35]. In order to avoid platelet activation during blood processing, a platelet inhibitory mixture was used as anticoagulant.…”
Section: Analytical Proceduresmentioning
confidence: 99%